Synaptic Interactions Between Serotonergic and Dopaminergic Systems in Parkinson's Disease - Marino, Gioia; Campanelli, Federica; Natale, Giuseppina; De Carluccio, Maria; Servillo, Federica; Ghiglieri, Veronica; Calabresi, Paolo (Current neuropharmacology, 2025)
Since both serotonergic and dopaminergic afferents densely innervate many parts of the central nervous system, intact crosstalk between serotonin (5-HT) and dopamine (DA) transmission is essential for regulating synaptic plasticity in the striatum (STR), prefrontal cortex (PFC), and hippocampus (HPC). Experimental models have provided strong evidence of a synergistic action of DA and 5-HT convergent release in PFC, HPC, and STR to modulate motor control, learning, and memory processes. In this review, we will discuss the mechanisms underlying the actions of agonists and antagonists of 5-HT and DA receptors on striatal synaptic plasticity in physiological conditions and Parkinson's disease (PD), a movement disorder in which an imbalance of these two neurotransmitter systems has been hypothesized. This review will also discuss the interactions between 5-HT and DA in PFC and HPC, with particular regard to the influence of this crosstalk on synaptic plasticity and learning. Finally, we will provide an overview of how stimulation or inhibition of DA and 5- HT receptors affects these neurotransmitter expression levels in the three brain regions of interest.